Quality of sweet-grape tomatoes grown under different nitrogen rates and sources - Chaves da Paixão, Caroliny Fatima; Silva dos Santos, Leonardo Nazário; Teixeira, Marconi Batista; Loureiro Soares, Frederico Antonio; Buranelo Egea, Mariana; Marques Vidal, Vitor; Batista Soares, Jaqueline Aparecida; Fernando Gomes, Luiz; Oliveira Fernandes, Larissa; Campos de Lira, Laura (Emirates Journal of Food and Agriculture, 2022)
Most sweet-grape tomatoes are marketed fresh; thus, sensorial characteristics are important for this vegetable. In this context, the objective of this work was to evaluate the technological quality based on the physical, chemical, and sensorial characteristics of sweet-grape tomatoes, the cultivar Carolina, grown under different nitrogen (N) sources (urea and organo-mineral) and N rates (50%, 75%, 100%, and 125%). The experiment was conducted in a greenhouse with controlled environment; the plants were grown in pots, using a drip irrigation system. A completely randomized experimental design was used, in a 2×4 factorial arrangement. The N soil fertilizer application was divided into three times: at 10, 17, and 24 days after the emergence of the plants. The fruits were harvested when presenting reddish color in the whole surface. The parameters evaluated were: weight, volume, specific volume, density, color, texture, total soluble solids, and sensorial characteristics. The physical characteristics of the sweet-grape tomatoes showed better results when using the organo-mineral treatment. The sensorial analysis showed better results when using the treatment with organo-mineral nitrogen fertilizer, which resulted in better marketable fruits higher than 70%. The treatment with urea resulted in marketable fruits higher than 50%. The N rate of 50% (urea or organo-mineral) resulted in greater acceptance by consumers, when considering the parameters appearance and firmness.